OUTCOMES-BASED EDUCATION: IS IT RIGHT FOR SOCIAL WORK? - Simpson, Barbara (Social Work/Maatskaplike Werk, 2010)
Outcomes-based education (OBE) has been very much in the news lately. Graeme Bloch’s book The toxic mix: what’s wrong with SA schools and how to fix it (2009) has received widespread coverage in the press, as have the results of the National Benching Tests Project (HESA, 2009), which demonstrated that a large number of entry-level students at tertiary institutions were not sufficiently competent in academic literacy, quantitative literacy or mathematics to succeed at university without substantial additional help. There are many complex reasons for the problems in the South African education system, but the suitability outcomes-based education to address the education challenges in South Africa has been seriously questioned.